2016
DOI: 10.3201/eid2202.151250
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Indicators for Ebola Patient Survival

Abstract: Odds of survival were greatest when first Ebola virus–positive blood sample collected had low viral load.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 20 publications
(21 reference statements)
4
41
0
Order By: Relevance
“…Clinical and laboratory factors at presentation that were associated with a fatal outcome included fever, weakness, dizziness, diarrhea, and elevated levels of blood urea nitrogen, aspartate aminotransferase, and creatinine. Age of >45 years and a plasma EBOV load of >10 8 genomes/mL were also associated with fatal outcomes, findings that were subsequently confirmed in other cohorts [31][32][33]. Our clinical study showed that the West African variant of EBOV causes predominately a gastrointestinal illness and focused attention on this aspect for control of disease spread, rather than on bleeding manifestations that predominated in prior outbreaks.…”
Section: Contributions Of Kgh To the Scientific Understanding Of The supporting
confidence: 74%
“…Clinical and laboratory factors at presentation that were associated with a fatal outcome included fever, weakness, dizziness, diarrhea, and elevated levels of blood urea nitrogen, aspartate aminotransferase, and creatinine. Age of >45 years and a plasma EBOV load of >10 8 genomes/mL were also associated with fatal outcomes, findings that were subsequently confirmed in other cohorts [31][32][33]. Our clinical study showed that the West African variant of EBOV causes predominately a gastrointestinal illness and focused attention on this aspect for control of disease spread, rather than on bleeding manifestations that predominated in prior outbreaks.…”
Section: Contributions Of Kgh To the Scientific Understanding Of The supporting
confidence: 74%
“…However, we observed that EBOV concentrations of 3.4 × 10 5 genomes/mL were present in experimentally infected nonhuman primates prior to the development of hallmark signs. In agreement with nonhuman primate testing, subsequent clinical testing demonstrated that the ReEBOV RDTs range of 1.0 × 10 5 -1.0 × 10 9 genomes/mL correlated well with threshold cycle times observed in patients with EVD during the course of acute EVD [25,27,28]. The ReEBOV RDT analytical validation presented here for FDA and WHO applications demonstrated the capacity to accurately detect EVD and provide a rapid, point-of-care test for EVD case triage and management.…”
Section: Discussionmentioning
confidence: 60%
“…156), which were important for compassionate use but were not wellconducted clinical studies. However, these trials do provide valuable information that can be used to improve future clinical validation of experimental therapies, particularly reiteration of the association between high viral load and reduced survival [208][209][210] . A number of studies have correlated nonsurvival at 90% or more if the viral load exceeds 6 log copies per millilitre [210][211][212][213][214] in untreated patients.…”
Section: Discussionmentioning
confidence: 99%